Tersilochinae (Hymenoptera: Ichneumonidae) of Costa Rica, part 2. Genera Megalochus gen. nov. and Stethantyx Townes - Khalaim, Andrey I.; Broad, Gavin R. (Zootaxa, 2013)
Two Costa Rican genera, Megalochus gen. nov. and Stethantyx Townes, are revised. These genera comprise a distinctive generic group that we refer to as the Stethantyx genus-group, veins Rs+2r and Rs angled more than 90°, vein 2rs-m and abscissa of M between 2rs-m and 2m-cu not or very weakly thickened, hind wing with vein cu1&cu-a (nervellus) more or less vertical, and prepectal carina with upper end not reaching anterior margin of mesopleuron, continuing above and backwards to the subtegular ridge. Both genera include medium sized to large species with body length 4.0 to 15.0 mm.           Megalochus comprises only the type species, M. grandis sp. nov., occurring in Costa Rica, Ecuador and southern Brazil. It is the largest representative of the subfamily, with a body length of 10.5 to 15.0 mm. Megalochus differs from Stethantyx, besides the larger body size, by the slenderer first metasomal segment, which is round in cross-section and lacking glymmae, propodeum and metapleuron with coarse rugae, and shortened antennae with strongly transverse flagellomeres.          Stethantyx is the dominant, most species-rich genus in the Costa Rican tersilochine fauna and probably in the Neotropical region. Twenty two species of this genus were discovered in Costa Rica, all are new: S. alajuela sp. nov., S. altamira sp. nov., S. aprica sp. nov., S. cacaoensis sp. nov., S. cartagoa sp. nov., S. cecilia sp. nov., S. curvator sp. nov., S. guanacasteca sp. nov., S. heredia sp. nov., S. limona sp. nov., S. mesoscutator sp. nov., S. niger sp. nov., S. nigrofemorata sp. nov., S. notaulator sp. nov., S. orosia sp. nov., S. osa sp. nov., S. propodeator sp. nov., S. pseudoorosia sp. nov., S. pseudoosa sp. nov., S. puntarenasa sp. nov., S. sanjosea sp. nov. and S. tenoriosa sp. nov.          A key for distinguishing the genera Megalochus and Stethantyx, and a key to 22 Costa Rican species of Stethantyx are provided.